Biochemical Diagnosis of Common Gene Mutations in Galactosemia - Farzaneh Mirzajani; Reza Mirfakhraei; Neda Naghib-Zadeh; Farah Nabati; Sasan Saki; Elham Talachian; Masoud Houshmand (University of Social Welfare and Rehabilitation Sciences, 2005)
Objective: Galactosemia is an inborn error of galactose metabolism that is inherited in an autosomal recessive trait. Classical galactosemia is caused by deficient activity of the galactose-1-phosphate uridyltransferase (GALT) enzyme that can result in galactosemia complications. Materials & Methods: 135 unrelated families, clinically suspected to galactosemia, were screened by qualitative measurement of galactose-1-phosphate uridyl transferase (GALT) activity in blood RBCs by using Beutler method. Results: Deficient enzyme activity (classical galactosemia) were confirmed in 16 families. All of these 16 families were submitted to the diagnosis of six common mutations in GALT gene including Q188R, K285N, S135L, L195P, X380R and Q169K by using PCR-RFLP method which resulted in detection of 68% of the mutated alleles. Eight patients were homozygote for Q188R mutation, while one patient homozygote for S135L mutation and one heterozygote for K285N mutation. Conclusion: Biochemnical diagnosis of Galactosemia in Grand infant hospital is very important and necessary.